WATER ADVANCING IN ASYMMETRICAL LINEAR CAPILLARY SYSTEM - Iosif Anshelevich Kipnis; Yury Mikhailovich Vernigorov (Advanced Engineering Research, 2013)
Actually, the water movement in the ‘soil-plant-atmosphere’ system is quite well studied. The main part of the ascending water in the plant goes through the xylem vessels. Higher plant xylem is a complex structure. To represent it as a set of ordinary vertical tubes is incorrect. Judging by the distribution model of fluid in the symmetrical capillary systems, the presence of lateral branches in the system leads to the water heightening in the vertical capillary compared to a single capillary of the equal radius. The analysis of N-level symmetric capillary model has shown that water may not reach the lateral capillaries even of the second level under the appropriate geometry of the system. The addition of an asymmetric lateral capillary to this system leads to a substantial water redistribution. The significance of asymmetrical elements can be seen on the example of young plants of a Nordmann fir tree (Abies nordmanniana). On the vertical trunk between parallel branches of different levels there are short lateral shoots that receive no further development. It can be assumed that these are asymmetry elements providing the water rise to the branch capillaries of the upper levels. The mathematical model of the water distribution in the capillary systems with asymmetrical capillary branches is built for an arbitrary number of the lateral capillaries levels. It is shown that the expansion in the number of both capillary branches in the level and levels leads to the water movement increase in the capillaries of the lower levels and in the vertical capillary. The presence of asymmetric elements in the branching capillary systems does not change the water distribution patterns in the branching symmetrical capillary systems. The revealed regularities can be considered as universal for the plant life.